EFFECT OF AMLODIPINE ON ENTEROPATHY INDUCED BY INDOMETHACIN IN RATS - ANNOUF, YARA; AL-LAHAM, SHAZA; AL-SHATTI, EYAD (International Journal of Current Pharmaceutical Research, 2020)
Objective: Non-steroidal anti-inflammatory drugs (NSAIDs) have become well known for causing gastroduodenal mucosal damage. In addition, they are also known to affect the small intestine in humans. Amlodipine is a third-generation dihydropyridine-type calcium channel blocker; it can inhibit inflammatory cytokines and enhance antioxidant defenses. The aim of this study was to evaluate the effect of Amlodipine on indomethacin-induced enteropathy in rats. Methods: Enteropathy was induced by subcutaneous indomethacin (Indo) prepared in 5 % sodium bicarbonate administrated at a dose rate of 9 mg/kg for two days at 24h intervals. Amlodipine (10 mg/Kg body weight po) was administrated for seven consecutive days beginning 24 h after the first Indo injection. Rats were sacrificed under ether anesthesia on the 8th day. The small intestinal injury was assessed by body weight loss, small intestine weight/length ratio, macroscopic damage, histological study, as well as by biochemical measurement of reduced glutathione (GSH), lipid peroxides and superoxide dismutase (SOD) activity in the small intestine tissue. Results: The results showed that Amlodipine didn't decrease body weight loss, it decreased small intestine weight/length ratio, macroscopic and microscopic small intestinal damage scores caused by administration of Indo. It also increased SOD activity and decreased lipid peroxidation. The effect on the level of GSH wasn't observed. No statistical significance was observed when previous findings were compared to Indo induced enteropathy group (p>0.05). Conclusion: Amlodipine didn't produce an obvious enhancement in enteropathy induced by Indo in rats.